In reply: spirituality, self-care, and social activity in the primary medical care of elderly patients : results of a cluster-randomized interventional trial (HOPES3) - Straßner, Cornelia (Deutsches Ärzteblatt, 2022)
We thank our correspondents for their critique of our study. We agree that the scientific definitions of spirituality and the way in which the term is individually understood and associated are heterogeneous. However, we do not see this as a confounder, because it was not the study’s objective to record spirituality statistically...